1976
DOI: 10.1042/bj1600413
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects in vivo of anti-insulin serum on rates of fatty acid synthesis and activities of acetyl-coenzyme A carboxylase and pyruvate dehydrogenase in liver and epididymal adipose tissue of fed rats

Abstract: Plasma insulin concentrations in fed rats were altered acutely by administration of glucose or anti-insulin serum. Rates of fatty acid synthesis in adipose tissue and liver were estimated from the incorporation of 3H from 3H2O. In the adipose tissue dehydrogenase and acetyl-CoA carboxylase were evident. In liver, although changes in rates of fatty acid synthesis were found, the initial activity of pyruvate dehydrogenase did not alter, but small parallel changes in acetyl-CoA carboxylase activity were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
204
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(215 citation statements)
references
References 24 publications
9
204
0
2
Order By: Relevance
“…One possible mechanism by which the reduction in PDH flux could affect proliferation is through reduced de novo lipogenesis, as fatty acid synthesis is critical for the production of new membrane during cell growth and proliferation. Indeed, PDH flux has been previously shown to correlate with lipogenesis (Stansbie et al 1976;Munday and Williamson 1981;Holness and Sugden 1990;Choi et al 2010) and we observed a 50%-65% decrease in the relative level of de novo lipogenesis in our MCF-10A models. Glucose-derived carbons, metabolized by PDH, are considered to be the primary source of AcCoA for lipogenesis in mammalian cells (Hatzivassiliou et al 2005).…”
Section: Discussionmentioning
confidence: 57%
“…One possible mechanism by which the reduction in PDH flux could affect proliferation is through reduced de novo lipogenesis, as fatty acid synthesis is critical for the production of new membrane during cell growth and proliferation. Indeed, PDH flux has been previously shown to correlate with lipogenesis (Stansbie et al 1976;Munday and Williamson 1981;Holness and Sugden 1990;Choi et al 2010) and we observed a 50%-65% decrease in the relative level of de novo lipogenesis in our MCF-10A models. Glucose-derived carbons, metabolized by PDH, are considered to be the primary source of AcCoA for lipogenesis in mammalian cells (Hatzivassiliou et al 2005).…”
Section: Discussionmentioning
confidence: 57%
“…This may mean that the PDH complex in muscle and BAT exhibits different insulin sensitivities, or that the time period of exposure to insulin has to be greater in the skeletal muscles than BAT for the same effect to be observed. The time of exposure and dose of insulin used in these experiments have previously been shown to be sufficient to elevate PDH complex activity in white adipose tissue [19].…”
Section: Resultsmentioning
confidence: 99%
“…For time points beyond time zero the fat pad was gently returned to the abdominal cavity and the wound was clipped. At specified time points animals were sacrificed, tissues were removed and the concentration of labelled lipids determined by the methods of Stansbie et al (1976).…”
Section: Methodsmentioning
confidence: 99%
“…The complete gastrointestinal tract was removed and homogenised in 5 ml of 3% (w/v) HC104. Lipids were extracted from organs and blood by the method of Stansbie et al (1976). The extracted fatty acids were dissolved in Optiphase scintillation fluid and the radioactivity determined as above.…”
Section: Methodsmentioning
confidence: 99%